Nf1 loss promotes Kras‐driven lung adenocarcinoma and results in Psat1‐mediated glutamate dependence - Xiaojing Wang; Shengping Min; Hongli Liu; Nan Wu; Xincheng Liu; Tao Wang; Wei Li; Yuanbing Shen; Hongtao Wang; Zhongqing Qian; Huanbai Xu; Chengling Zhao; et al. (EMBO Molecular Medicine, 2019)
Abstract Mutations to KRAS are recurrent in lung adenocarcinomas (LUAD) and are daunting to treat due to the difficulties in KRAS oncoprotein inhibition. A possible resolution to this problem may lie with co‐mutations to other genes that also occur in KRAS‐driven LUAD that may provide alternative therapeutic vulnerabilities. Approximately 3% of KRAS‐mutant LUADs carry functional mutations in NF1 gene encoding neurofibromin‐1, a negative regulator of focal adhesion kinase 1 (FAK1). We evaluated the impact of Nf1 loss on LUAD development using a CRISPR/Cas9 platform in a murine model of Kras‐mutant LUAD. We discovered that Nf1 deactivation is associated with Fak1 hyperactivation and phosphoserine aminotransferase 1 (Psat1) upregulation in mice. Nf1 loss also accelerates murine Kras‐driven LUAD tumorigenesis. Analysis of the transcriptome and metabolome reveals that LUAD cells with mutation to Nf1 are addicted to glutamine metabolism. We also reveal that this metabolic vulnerability can be leveraged as a treatment option by pharmacologically inhibiting glutaminase and/or Psat1. Lastly, the findings advocate that tumor stratification by co‐mutations to KRAS/NF1 highlights the LAUD patient population expected to be susceptible to inhibiting PSAT1.